Characteristics and challenges of the clinical application of brain–computer interface technology. - Fujiwara, Gaku; Saotome, Chikako (Health & Technology, 2026)
Background: Brain–computer interface (BCI) technology is an emerging technology that makes communication possible and supports motor functions by analyzing brain activity and transmitting control signals to external devices. It has potential as a therapeutic or assistive tool for patients with severe conditions, such as paralysis. Although the number of BCI-related patents has been increasing, clinical applications remain limited. The purpose of this study was to clarify the status of BCI patent applications and clinical trials, analyze their characteristics, and identify the challenges in clinical implementation. Methods: Patent data were obtained from Espacenet using the terms "brain–computer interface" and "brain–machine interface" and categorized as invasive or noninvasive based on international patent classifications. Applications were analyzed based on applicant nationality, type, collaboration status, and invasiveness. Clinical trial data were collected from ClinicalTrials.gov and the Chinese Clinical Trial Registry. Trials were similarly classified and analyzed by country, target disease, treatment content, sample size, trial status, and publication status. Results: A total of 4216 BCI-related patent applications were identified, of which 2366 (56.1%) were from China and 752 (17.8%) from the United States (US). Most Chinese applications were filed by universities, showing a sharp increase after 2021. In contrast, among the 195 clinical trials, 138 (70.8%) were conducted in the US and Europe, whereas only 23 (11.8%) were conducted in China. Invasive technologies accounted for 33 (16.9%) of the trials. Noninvasive trials mainly focused on stroke rehabilitation, whereas invasive trials targeted the control of machines or computers for patients with quadriplegia. Most trials were small, with fewer than 50 participants. Among the invasive trials, 24 out of 33 (72.7%) involved five or fewer participants. Overall, 68 clinical trials had been completed (34.9%). Whereas 63 of 162 noninvasive trials (38.9%) had reached completion, only 6 of 33 invasive trials (15.2%) had been completed, and 18 (54.5%) were still recruiting participants. Conclusion: Patent and clinical trial trends in BCI vary by region and invasiveness. Although China has the most patent applications, clinical implementation is limited. In contrast, the US and Europe are progressing toward practical use, although invasive technologies face recruitment challenges. These findings highlight the important issues for the development and application of BCI.